TEACHING ENGLISH FOR YOUNG LEARNERS USING A DIGITAL COMIC STRIP - Adi Ana, I Ketut Trika (Universitas Pendidikan Ganesha, 2015)
Abstract: Teaching English for Young Learners Using a Digital Comic Strip. Since young learners get bored easily, English teachers should be creative in designing the instruction in order to make it interesting for the students. One of the ways that can be done by the English teachers to make their teaching and learning process becomes an interesting activity is by providing good teaching media. It is believed that young learners love story and colorful teaching media. Therefore, this article aims at explaining how to create a colorful digital comic strip and how to use it for teaching English. Specifically, this article discusses about: (1) the role of story in teaching English for young learners; (2) how to design and develop a digital comic strip; (3) how to teach English for young learners using a digital comic strip; and (4) the benefits of teaching English for young learners using a digital comic strip. It is expected that this article could give enough information for those English teachers who want to teach English for young learners using a digital comic strip. Keywords: comic strip, instructional media, young learners Abstrak: Pembelajaran Bahasa Inggris untuk Peserta Didik Anak-Anak Menggunakan Komik Strip. Para guru yang mengajar Bahasa Inggris untuk anak-anak hendaknya kreatif dalam mendesain sebuah pembelajaran untuk menciptakan pembelajaran yang menarik bagi peserta didik. Hal tersebut karena peserta didik anak-anak sangat cepat bosan. Salah satu cara yang dapat dilaku-kan untuk mencipatakan pembelajaran yang menarik adalah dengan membuat media pembelajaran yang bagus. Anak-anak biasanya menyukai cerita dan media pembelajaran yang berwarna-warni. Untuk itu artikel ini akan menjelaskan mengenai cara mengembangkan komik strip digital berwarna dan strategi untuk mengajar Bahasa Inggris menggunakan komik strip digital tersebut. Secara spesi-fik, artikel ini akan membahas mengenai: (1) peranan cerita dalam pembelajaran Bahasa Inggris un-tuk peserta didik anak-anak; (2) cara mendesain dan mengembangkan komik strip digital; (3) strate-gi mengajar menggunakan komik strip digital; dan (4) manfaat pembelajaran bahasa Inggris meng-gunakan komik strip digital. Diharapkan artikel ini dapat memberikan informasi yang cukup bagi guru yang tertarik untuk mengajar Bahasa Inggris menggunakan komik strip digital. Kata-kata Kunci: komik strip, media pembelajaran, peserta didik kanak-anak,